Kinetic Resolution of 2‐N‐Acylamido Tertiary Allylic Alcohols: Asymmetric Synthesis of Oxazolines - Pan, Yongkai; Jiang, Qianwen; Rajkumar, Subramani; Zhu, Chaofan; Xie, Jinglei; Yu, Shaoze; Chen, Yunrong; He, Yu‐Peng; Yang, Xiaoyu (Advanced synthesis & catalysis, 2021)
A series of cyclohexyl‐fused SPINOL‐derived phosphoric acids (Cy‐SPA) have been developed to catalyze the kinetic resolution of 2‐N‐acylamido tertiary allylic alcohols, providing access to chiral oxazolines bearing C‐2 alkyl substituents with high enantioselectivities (with s‐factors up to 153). Gram‐scale reaction with 1 mol% catalyst loading and transformations of the chiral products demonstrates the value of these methods.